Self Compassion dan Dukungan Sosial: Kunci Mengatasi Quarter Life Crisis Gen Z - Setyowati S, Ninda Widya; Saragih, Sahat; Prasetyo, Yanto (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract This study was conducted to explore the relationship between self compassion and social support and the quarter life crisis for Gen Z social media users. The application of correlational quantitative methods was used in this study involving 183 participants aged 20–27 years. Research data was obtained through distributing Likert scale-based questionnaires which included three main variables: self compassion, social support, and quarter life crisis. Research findings indicate a significant negative relationship between self compassion and social support and quarter life crisis. Self compassion encourages individuals to be more accepting of life's challenges, while social support provides a sense of emotional security and reduces psychological stress. The variables self compassion and social support simultaneously play an important role in supporting Generation Z in facing changes towards adulthood. Keywords: Generation Z; quarter life crisis; self compassion; social media; social support Abstrak Studi ini dilakukan untuk mengeksplorasi keterkaitan antara self compassion dan dukungan sosial dengan quarter life crisis bagi pengguna media sosial Gen Z. Penerapan metode kuantitatif korelasional digunakan dalam studi ini dengan melibatkan 183 partisipan berusia 20–27 tahun. Data penelitian diperoleh melalui penyebaran kuesioner berbasis skala Likert yang mencakup tiga variabel utama: self compassion, dukungan sosial, dan quarter life crisis. Temuan penelitian mengindikasikan hubungan negatif yang signifikan antara self compassion dan dukungan sosial dengan quarter life crisis. Self compassion mendorong individu untuk lebih menerima tantangan hidup, sementara dukungan sosial memberikan rasa aman emosional dan mengurangi stres psikologis. Variabel self compassion dan dukungan sosial secara bersamaan memegang peranan penting dalam mendukung Generasi Z menghadapi perubahan menuju kedewasaan. Kata kunci: dukungan sosial; Generasi Z; media sosial; quarter life crisis; self compassion